Routine immunofluorescence detection of Ro/SS-A autoantibody using HEp-2 cells transfected with human 60 kDa Ro/SS-A. Issue 9 (1st September 1999) - Pollock, W; Toh, B H
Abstract : BACKGROUND: Ro/SS-A autoantibodies associated with systemic lupus erythematosus (SLE) and Sjögren syndrome may be missed during routine screening for antinuclear autoantibodies (ANA) by immunofluorescence using HEp-2 cells. AIMS: To investigate the use of HEp-2 cells transfected with human 60 kDa Ro/SS-A for routine detection of these antibodies. METHODS: 10, 500 sera were screened at a dilution of 1:200 for Ro/SS-A antibodies, identified by intense immunofluorescence staining in 10-15% of hyperexpressing cells of either the nucleus and nucleolus combined or the nucleus alone. RESULTS: Ro/SS-A antibodies were identified in 160/2100 ANA positive sera (8%), of which seven were ANA negative (titre < 200) and 33 had weak ANA titres (200) in 85-90% of non-hyperexpressing "background" cells. Enzyme linked immunosorbent assay (ELISA) confirmed the presence of Ro/SS-A antibodies in 110 newly diagnosed Ro/SS-A positive sera. Of these, 50 reacted with Ro/SS-A, 51 with Ro/SS-A and La/SS-B, and nine with Ro/SS-A and other extractable nuclear antigen (ENA) specificities. Fifteen sera which did not show Ro/SS-A antibodies by immunofluorescence tested positive for Ro/SS-A by immunodiffusion, counter-immunoelectrophesis, or ELISA; of these, 14 had ANA titres > 200. Clinical data from 95 Ro/SS-A positive patients showed that 52% had SLE, 24% Sjögren syndrome, 8% rheumatoid arthritis, and 16% other diseases. CONCLUSIONS: (1) HEp-2 cells transfected with human 60 kDa Ro/SSA are useful for routine immunofluorescence detection for Ro/SS-A antibodies with a positive predictive value of 100%; (2) sera positive for Ro/SS-A antibodies by immunofluorescence should be tested for ENA by other methods because > 50% of these sera will have another ENA reactivity in addition to Ro/SS-A; (3) detection of Ro/SS-A by immunofluorescence may be missed in the presence of high titre ANAs; (4) with a detection sensitivity of 91%, a negative immunofluorescence results for Ro/SS-A does not exclude the presence of this autoantibody.